Test Of Reading Readiness in typically developing Odia speaking children(TORR-O) - Mishra, Anima; B S, Premalatha (Journal of All India Institute of Speech and Hearing, 2013)
The objective of the current study was to develop a screening tool in Odia for reading readiness in preprimary children which was to be named as TORR-O. The subjects of the study were 248 children (135 boys; 113 girls) speaking Odia as mother tongue and studying in schools with Odia as medium of instruction. The study was conducted in 2 phases. Phase-I was Pilot Study, as a part of which TORR-O was constructed with 30 questions which were designed to assess skills like print identification, shape and color matching, visual discrimination, letter recognition, alliteration, rhyming, blending, deletion and segmentation through a series of picture pointing tasks. The test was then administered on 12 children between the ages of 3.5 to 4.5 years. Based upon the results obtained, appropriate modifications were made. In Phase II, the Main Study, the revised version of the test was then administered to 168children between 3.5 to 4.5 years from various Odia medium schools across the two districts of Orissa. Item analysis and analysis of correlation was done. Item analysis included computation of discriminative power (DP) and difficulty index (DI) of the test items. DP gave a measure of competence of the test material to discriminate between poor and good readers and DI indicated difficulty of the test items. It was found that 17 test items were within the DP range of 0.2 to 0.8 and 21 were within the DI range of 30 to 70%. ANOVA was done to arrive at a correlation between age of children and reading readiness skills which concluded that the above mentioned skills are age dependent. The test findings concluded that the TORR-O can be used to assess reading readiness in typically developing Odia speaking children between ages of 3.5 years to 4.5 years excluding the items out of the DI-DP range.